Oil nano-emulsion formulation of Azadirachtin for control of Bemisia tabaci gennadius - Kamarudin, Noorhazwani (2013)
Current water emulsion insecticides only provide limited control of Bemisia tabaci. Oil droplets were found to be more effective as they spread much better on leaf surfaces compared to either water alone or water that contained adjuvant. Thus oil nano-emulsion formulation derived from azadirachtin was developed as an effort to control the population of whiteflies, B. tabaci. Oil nano-emulsion system was developed for insecticide formulations by constructing ternary phase diagrams with 70% (w/w) emulsion system constituted of non-ionic surfactant(s), carrier, water, and 30% (w/w) neem oil as an active ingredient. The non-ionic surfactant was alkylpolyglucosides while carrier or oil phase was dimethylamide. Ternary phase diagrams of the mixed surfactant systems MBL510H: MBL530B at mixed surfactant ratios (MSRs) of 5:5, 6:4, 7:3, 8:2, 9:1 exhibited larger isotropic (I) phase than the single surfactants of either MBL510H or MBL530B. The points were selected from the ‘I’ phase and homogenous region for preformulation. Most of the points selected were from regions with high proportion of oil, low proportion of water and adequate proportion of surfactant to mix with active ingredient and to form water-in-oil (W/O) emulsion. Sixteen formulations miscible with neem oil were selected. In the stability study, all the selected formulations were stable under centrifugation and storage at room temperature (25˚C). However, at 54°C after 14 days storage, F3, F7, F9, F10, and F12 showed phase separation,transformed to two opaque phases. The mean particle size of nano-emulsions ranged between 150.00 and 450.00nm except for F9 with mean particle size of 640.44nm. All sixteen formulations showed surface tension lower than water (72.00mN/m). The formulation F14 (29.90mN/m), F15 (29.93mN/m) and F16 (29.86mN/m) showed lower surface tension compared to other formulations. The zeta potential values of F14 (39.60mV), F15 (39.20mV) and F16 (38.80mV) were higher compared to the other formulations. The value is related to the stability of colloidal dispersions and high zeta potential value will confer stability. In the biological activity study, the adult B. tabaci were used to test the toxicity of the oil nano-emulsion formulation. The result showed the mortality of the adults was higher with the increase of time exposure. The mortality rate of B. tabaci showed that the oil nano-emulsion formulations gave excellent efficacy with LC50 value of 3.70ppm at 96 h after treatment. In the measurement of spread area study, three different levels of formulation toxicities were used to determine the spreading coefficient and evaluate the mode of action of the formulation on the early nymphal instar’s B. tabaci. The studies have proved the interaction between spread area and mortality rate. The larger the spread area of the droplet result in increased of mortality. In this study, F15 formulation with low mean lethal concentration gave the larger spread area on the leaves surfaces. As a result, the formulation also gave highest mortality rate on early nymphal instar of whiteflies due to the spreading ability of this formulation. This finding has proved the mode of action of oil nanoemulsion formulation in killing the early nymphal instars of B.tabaci by giving wider coverage of active material on leaves surface and brings larger areas of cuticle into contact with the insecticides, resulting in better retention and enhanced the biological effect.